A importância do capital humano na eficiência técnica e na produtividade total dos fatores do setor canavieiro do Brasil - Alves, Hellen Cristina Rodrigues (2008)
The study shows the importance of human capital in technical efficiency and productivity of factors of sugar cane in Brazil. It was considered as analysis units the producers State of Brazil. The methodology used was based in analysis of stochastic frontier and the malmquist productivity index. The results shows that the states of the South and Mid-West are generally more efficient, with partial productivity of land and labor-higher than those from the South and Northeast. It was clear the importance of human capital in technical efficiency and productivity which led the main conclusion that the education level of workers is an important variable in policies designed to increase productivity of sugar cane.